(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Our present era is witnessing a contemporary global civilization, for which museums are one of the most important arenas, manifestations, and glories. Countries of the world are keen to establish museums, increase their number, diversify their savings, raise their level, make good use of them, and be proud of them and their precious treasures that date back to diverse eras and multiple civilizations, talk about them, and attract tourists to visit them and see their holdings. Until tomorrow, the museum (the criterion for the advancement of nations and the measure of their progress), and visiting them and knowing their details is evidence of the individual’s cultural awareness and the focus of his social conversations. In addition to the diversity of cultures of the visitor to museums and to meet his multiple needs in our current era, which requires the availability of the latest means and services that meet his knowledge desires in the areas of cultural, scientific and civilizational components. The museum has become in developed societies (the mirror of society) through the statistics of the number of visitors, which is one of the most important criteria for the sophistication and progress of societies and their strong desire to know human heritage and their concern for their cultural property.